PROGRAM PEMANFAATAN DANA DESA UNTUK PEMBANGUNAN MASYARAKAT: (STUDI KASUS DESA TANI BHAKTI KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA) - Yanti, Wilda; Laila, Alif; Hasriadi, L.M. (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
Village Funds are a government program to support and realize village development, named through Village Funds as a source of Village income. Law Number 6 of 2014 concerns the authority of the village to use these funds from the APBN. This research aims to study Village Funds (DD) used in Tani Bhakti Village, Loa Janan District, Kutai Kartanegara Regency as the principles of Village development in the Utilization of Village Funds. The results showed that using Village Funds to support the infrastructure developments in Tani Bhakti Village has been effective proven by the number of development programs. Community involvement in the use of village funds is quite good in preparing the plan and development work, even up to the development stage of the program. Village development activities include managing village health posts and the police, counseling on stunting prevention, providing milk assistance to toddlers, and health facilities, developing village health cadres, coaching and training for women's groups, and improving road construction. The Tani Bhakti Village Government provides direct cash assistance (BLT) to families who do not have decent jobs, widowed/elderly women, and orphaned children. All programs are carried out with cooperation, even before implementation there is called MUSDES (Village Conference) as the opportunity to express opinions and propose prospective programs in terms of infrastructure and community empowerment.